Differentiated Training System for Shipping Service Professionals: The Case of Shanghai International Shipping Center - Sun, Ming; Yan, Ru; Yuan, Kebiao; Vortia, Midakpe P. (Asia Pacific Economic and Management Review, 2026)
To address the dual challenges of intelligent and green transformation in the global shipping industry, this study conducts an in-depth analysis of Shanghai, an emerging global shipping hub, as its primary case study. It identifies core issues within the existing system, including homogenized training models, outdated curriculum content, and delayed responsiveness to industry demands. These issues are particularly evident in the inability to deliver precise, differentiated training for two critical groups: foundational talent and high-end professionals. To address this structural contradiction, this study proposes a systematic differentiated training framework centered on deepening tailored development, drawing on Singapore's international best practices. This framework aims to establish a standardized support system for foundational talent and an innovation-driven ecosystem for high-end professionals, outlining specific reform pathways across three dimensions: training models, curriculum systems, and industry-education integration. Finally, through systematic initiatives such as a lifelong learning certification system and the development of cutting-edge shipping innovation, this framework will propel Shanghai toward establishing a shipping service talent ecosystem that aligns with future industry trends, features a clear structure, and possesses resilience. This research does not only provide strategic guidance for Shanghai to overcome structural talent bottlenecks and achieve a leap in capability, instead, it also offers a universally applicable framework for categorized training and system upgrades to emerging shipping hubs worldwide facing similar transformation challenges.